El catolicismo chileno entre los 40s y los 60s. Un estudio a través de tres polémicas: la Ley Maldita, la huelga de Molina y las cartas pastorales de 1962 - Botto Stuven, Andrea (Anuario de Historia de América Latina, 2025)
Hispanic-American Catholicism has faced numerous changes in the last fifty years due to events in the international Church and to internal challenges in each of the countries where it is present. Chilean Catholicism presents itself as a privileged scenario to study these transformations, given that the Chilean Church was considered in the last century as one of the most progressive in Latin America, and that attitude had profound consequences among the country’s Catholics. This study focuses on Chile, but we believe it can be relevant to help understand the processes that Catholicism in our continent has experienced in the last century, as well as an instance of discussion about the history of the Catholic laity and the Church. The objective is to contribute to the history of Catholic ideas and intellectualism through a study of thought and debates within national Catholicism in years of profound structural changes marked by the new protagonism of the laity, the emergence of a markedly more progressive clergy, and the great ecclesial transformation that was Vatican II. We want to see how both the Catholic laity and ecclesial sectors continued to develop a strong presence in the public sphere, participating in discussions and debates that sought to improve society and the state. The proposal of this work is to elucidate the main flags of struggle that arose within the Chilean Catholic world, about how to interpret and disseminate the Social Doctrine of the Church and in what way to put it into practice, focusing on three specific moments in which Catholicism and politics intersected, causing debates and deep ruptures within the Chilean Catholic world. Those three moments are: the discussion around the so-called "The Coursed Law," which proscribed the Chilean Communist Party in 1948; the Molina peasant strike, which occurred in late 1953; and the publication of the two controversial pastorals of the Chilean Episcopate in 1962. Thus, the topic is inserted into a broader approach that investigates the close relationship between catholicism and politics in Chile, despite the separation between Church and State in 1925, to insist on its persistent influence on the affairs of civil society and the growing secularization of the Chilean clergy, especially in the chronological period studied.